THE USE OF THE “ARAB BETA” APPLICATION IN LEARNING AL-ASHWAT AL-‘ARABIYYAH FOR GRADE VII STUDENTS OF MTS DARUL MUSTHOFA, SELUMA - Haryono, Abdullah; Sopian, Asep (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to develop the ARAB BETA learning application as an interactive medium to enhance students’ pronunciation skills in al-ashwat al-‘Arabiyyah (Arabic phonetics). The background of this research is based on the limitations of existing learning applications such as Duolingo and Kahoot, which do not offer specific features for intensive practice in the pronunciation of Arabic letters. The method used is Research and Development (RD) referring to the Borg and Gall development model. The research subjects were seventh-grade students at MTs Darul Musthofa Seluma during the second semester of the 2024/2025 academic year. Data collection techniques involved validation tests conducted by subject matter experts, media experts, and language experts, as well as limited trials involving students. The research findings indicate that the ARAB BETA application is feasible for use as an interactive learning medium in ilmu ashwat, with an average validation score categorized as